2022
DOI: 10.1080/15384101.2022.2029996
|View full text |Cite
|
Sign up to set email alerts
|

STING agonist enhances the efficacy of programmed death-ligand 1 monoclonal antibody in breast cancer immunotherapy by activating the interferon-β signalling pathway

Abstract: This document certifies that the paper listed below was edited and proofread for proper English language, grammar, punctuation, spelling, and overall style by one or more than one highly qualified native speakers at Bullet Edits. All of the suggested amendments were tracked with the Microsoft Word "Track Changes" feature. Therefore, the author had the option to reject or accept each change individually.Bullet Edits is a registered company headquartered in the UK with a global presence.We offer a range of editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In addition, EMT can be inhibited by Wnt/beta-catenin pathway, thereby inhibiting cancer cell metastasis [ 56 ]. It has been demonstrated that STING agonists can inhibit the growth and proliferation of breast cancer cells and can be used not only in the treatment of breast cancer, but also in combination with atenrizumab to enhance the efficacy of immunotherapy [ 57 ]. However, persistent overactivation of STING induces chronic inflammation and involves a wide range of autoimmune diseases [ 38 , 41 ], and whether its activation induces a negative feedback loop that inhibit the action of STING agonists remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EMT can be inhibited by Wnt/beta-catenin pathway, thereby inhibiting cancer cell metastasis [ 56 ]. It has been demonstrated that STING agonists can inhibit the growth and proliferation of breast cancer cells and can be used not only in the treatment of breast cancer, but also in combination with atenrizumab to enhance the efficacy of immunotherapy [ 57 ]. However, persistent overactivation of STING induces chronic inflammation and involves a wide range of autoimmune diseases [ 38 , 41 ], and whether its activation induces a negative feedback loop that inhibit the action of STING agonists remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…As a mechanism of stimulating STING in immune cold tumors, either 2′3′-cGAMP or agonists (small molecules that activate STING) have been implemented to stimulate interferon expression and promote an anti-tumor immune response (Deng et al, 2014). Using the 4T1 TNBC model, the STING agonist, cyclic diguanylate, lead to induction of IFNβ expression which was coupled to an increase in activation of STING and its downstream effectors (Yin et al, 2022). Cyclic diguanylate synergized with atezolizumab (anti-PDL1) to reduce tumor growth through activation of cytotoxic T-cells and suppression of T regs (Yin et al, 2022).…”
Section: Induction Of Ifn Expression Through Sustaining Sting Activationmentioning
confidence: 99%
“…Using the 4T1 TNBC model, the STING agonist, cyclic diguanylate, lead to induction of IFNβ expression which was coupled to an increase in activation of STING and its downstream effectors (Yin et al, 2022). Cyclic diguanylate synergized with atezolizumab (anti-PDL1) to reduce tumor growth through activation of cytotoxic T-cells and suppression of T regs (Yin et al, 2022). Other work on a HER2+ model using the STING activator, ADU-S100, demonstrated that STING activation can induce tumor regression as well as protect against tumor rechallenge in nontolerized animals (Foote et al, 2017).…”
Section: Induction Of Ifn Expression Through Sustaining Sting Activationmentioning
confidence: 99%
“…STING agonists exhibited effective antitumor activity, including cyclic di-guanosine monophosphate and synthetic cyclic dinucleotide derivatives [ 106 ]. A number of studies demonstrated that STING agonists combined with a cancer vaccine or delivery platform induced a potent inflammatory response and modulated the tumor microenvironment by increasing proliferation of CD4+ T cell [ 107 , 108 , 109 , 110 ]. Although STING agonists might cause some systemic toxicity, the novel strategies of combined therapy would accelerate their application as a cancer vaccine adjuvant.…”
Section: Adjuvantsmentioning
confidence: 99%